Experimental study on microscopic residual oil distribution and dredging direction of water-driven zoned utilization in narrow-channel reservoirs - Jia, Pin; Sun, Qiang; Feng, Haoran; Li, Yang; Liu, Bangdan (Frontiers in Earth Science, 2025)
In the process of water-driven development of narrow-channel oil reservoirs, the comprehensive water cut rate rises quickly, showing the development characteristics of “flooding everywhere in the river channel, but the degree of recovery is low”, and the underground oil and water distribution is complicated due to its special narrow strip sand body spreading and long-term water-injection development. Therefore, there is an urgent need to research the water-water drive law of narrow-channel reservoirs, to clarify the distribution law of microscopic residual oil and the degree of water-driven utilization. In this paper, taking BZ offshore narrow channel reservoir as the research object, a full-view microscopic water drive physical simulation experiment platform was established and microfluidic experiments were carried out. Based on the physical simulation experiment of microscopic residual oil distribution, the oil-water distribution images of each stage in the water flooding process are obtained. It is found that this type of reservoir has a serious fingering phenomenon in the early stage of water drive, and the residual oil can be classified as contiguous, porous, membrane, strip, and drop, and evolves in the above order. The direction of dredging in the weakly active zone is mainly to change the direction of fluid flow, the direction of dredging in the medium active zone is equivalent to the effect of changing the direction of fluid flow and optimizing the injection and recovery parameters, and the impact of dredging in the strongly active zone is mainly to optimize the injection and recovery parameters. This study reveals the characteristics of microscopic water drive, clarifies the type of microscopic residual oil and its evolution process, and clarifies the distribution of residual oil and the dredging effect under the utilization of different water-driven zones, which is of certain guiding significance for the development and adjustment of the same type of reservoirs.